2020
DOI: 10.1101/2020.01.16.909952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A hybrid spectral library combining DIA-MS data and a targeted virtual library substantially deepens the proteome coverage

Abstract: Data-independent acquisition mass spectrometry (DIA-MS) is a rapidly evolving technique that enables relatively deep proteomic profiling with superior quantification reproducibility. DIA data mining predominantly relies on a spectral library of sufficient proteome coverage that, in most cases, is built on data-dependent acquisition-based analysis of the same sample. To expand the proteome coverage for a pre-determined protein family, we report herein on the construction of a hybrid spectral library that supple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…2C). Although we previously demonstrated this strategy in processing data from a few brain regions as a proof of a concept (21), our current study proved that this hybrid spectral library can deepen the GPCR subproteome coverage to surpass a large-scale project-specific DDA library.…”
Section: Profiling the Transmembrane Proteome In Multiple Mouse Brain...mentioning
confidence: 63%
“…2C). Although we previously demonstrated this strategy in processing data from a few brain regions as a proof of a concept (21), our current study proved that this hybrid spectral library can deepen the GPCR subproteome coverage to surpass a large-scale project-specific DDA library.…”
Section: Profiling the Transmembrane Proteome In Multiple Mouse Brain...mentioning
confidence: 63%
“…First of all, we needed to determine KRT17 expression. DIA-MS is a proteomic methodology for deep and proteome-wide pro ling with high accuracy and reproducibility in proteomic quanti cation [22,23], we used DIA-MS to investigate the DEPs, and the result showed that the expression of KRT17 was up-regulated in ESCC tumor tissues, the differential expression was further determined by the data obtained from GEPIA. Also, the overall survival of ESSC patients was also closely related with KRT17 levels.…”
Section: Discussionmentioning
confidence: 99%
“…While this increased complexity makes the handling and analysis of DIA data more laborious, it has been demonstrated that the quanti cation by DIA is more robust compared to DDA. Recently, DIA has reached a protein coverage that is comparable to, or even exceeds, the one of DDA 2,3 .…”
Section: Introductionmentioning
confidence: 99%